Effect of mach number on stiffness and damping derivatives for oscillating hyersonic non-planar wedge - Crasta, Asha; Khan, Sher Afghan (International Organization of Scientific Research (IOSR) Journals, 2014)
similitude has been obtained for a pitching oscillating Non planar wedge with attached bow shock at high angle of attack in hypersonic flow. A strip theory in which flow at a span wise location is two dimensional and independent of each other is being used. This combines with the similitude to lead to a one dimensional piston theory. Closed form of simple relations is obtained for stiffness and damping derivatives in pitch. The present theory is valid only when the shock wave is attached with the nose of the wedge. With the increase in semi vertex angle of the wedge the stiffness as well as the damping derivatives assumes a high value, and the center of pressure of the wedge also shift towards the trailing edge. Whereas, with the increase in Mach number both stiffness and damping derivative assumes lower values. For higher Mach numbers the stability derivatives become independent of Mach number. From the theory developed some of the results are obtained for wide range of Mach number with remarkable computational ease.